Structural Optimization of Logistics Distribution System Based on Characteristic State Space - Yongyan Bao; Delun Wang; Yuan Sun; Hao Zheng (Journal of Advanced Transportation)
In this paper, resource flow variables are extracted from the internal structural features of the logistics distribution process and a new method for optimizing the internal structure of the logistics distribution system by using the characteristic state space is proposed. The characteristic state equation is constructed to represent the input and output resources of each basic logistics activity. The basic logistics activity equation is iterated according to the resource flow, and the implementation of the basic logistics process is visually and quantitatively expressed in the form of the characteristic state matrix. According to the nature of the characteristic state space, the optimization problem of the logistics distribution system is transformed into a critical path-planning problem, the gradient calculation of the objective function is solved, and an improved genetic algorithm is proposed. This accelerates the convergence speed of the algorithm and reduces the running time of the optimization process. Taking a listed logistics distribution enterprise as an example, the optimization algorithm is verified, which proves the advantages of the algorithm and provides a new method and theoretical basis for the analysis and optimization of the logistics distribution system.